Conflict Landscapes of the Great War: The Spatial and Ecological Dimension of Military History - Nagornaia, Oksana; Lingen, Kerstin von (Quaestio Rossica, 2023)
The spatial and environmental dimension of WWI has recently taken the central place in academic debates on the military history of the “short twentieth century”. At present, the large-scale conflict of humanity and nature under totalized warfare is recognized as no less significant to the existential experience of combatants and civilians than actual battles. Functioning as a demiurge, the Great War created and re-molded landscapes, accelerated development trends shaped during the industrial era, triggered the construction and demolition of infrastructure, and determined the resource policy, economic practices, and language constructs of national communities during subsequent historical periods. Textual and visual narratives of the war feature the following three dimensions of the environment: a subject and adversary (sometimes even more dangerous than the real enemy); an object of destruction, invasion, and ordering; and an anthropological construct defining behavioral strategies and the memorial culture relating to the conflict. Modern researchers share a unanimous opinion that the pivotal role of the clash between humanity and the environment during WWI for subsequent historical development is paradoxically at odds with the degree to which the clash has been studied. This may be linked with the fact that the multidimensionality of militarized landscapes would require a research methodology incorporating elements of military history, ecology, anthropology, archaeology, geology (landscape studies), and cultural geography. Such a creative symbiosis has become possible only recently, owing to the adoption of the interdisciplinary approach by military historians. The gradual uptake of innovative study techniques has resulted in the uneven development of the spatial and environmental history of the First World War as a research field: at present, the best-studied locations are confined to the western front and, partly, the colonial periphery. This publication presents a review of the recent conceptual publications by authors developing this research avenue and seeks to identify the heuristic potential of the concepts “Anthropocene”, “belligerent landscapes”, “landscape biographies”, and “layered landscapes”, including their applicability to the history of the Eastern Front of the First World War.